The Sweetest Dream: Love, Lies, & Assassination - Palmer, Bryan D. (Labour / Le Travail, 2009)
The article reviews the book, "The Sweetest Dream: Love, Lies, & Assassination," by Lillian Pollak.
Keywords: ASSASSINATION; BOOKS -- Reviews; Book reviews; Business And Economics--Labor And Industrial Relations; History--History of North And South America; Nonfiction; Novels; POLLAK, Lillian; SWEETEST Dream: Love, Lies & Assassination, The (Book)